Design of shape memory alloy coil spring actuator for improving performance in cyclic actuation - Koh, Je Sung (Materials, 2018)
Performance of the shape memory alloy (SMA) coil spring actuator in cyclic actuation as an artificial muscle is strongly related to the mechanical design of the coil geometry. This paper proposes a practical design method for improving the frequency and efficiency of the SMA coil spring actuator; by designing the SMA coil spring to have large index (coil diameter/wire diameter) and pitch angle (LIP), cooling characteristics can be improved (increasing the actuation frequency) and large deformation can be obtained. The LIP design process is based on the two-state static model that describes the displacement-force relationship of the SMA coil spring in two states-a fully austenite phase and a fully martensite phase. The design process gives accurate design parameters of the SMA coil spring actuator that satisfy the required stroke and force. The model of the fully martensite phase of the SMA coil that includes the stress-induced detwinning enables the use of maximum shear strain of the SMA. The design method reduces the mass of an SMA without changing the stroke and increase the power density and efficiency. The cyclic actuation experiments demonstrate that the LIP design doubles the maximum frequency of SMA coil actuator with one-sixth the mass of the non-LIP design.
Keywords: Artificial muscle; Cooling characteristics; Improving performance; Practical design method; Shape memory alloy actuators; Shape memory alloys(SMA); Soft actuators; Soft robotics; Artificial muscle; Shape memory alloy actuator; Soft actuator; Soft robotics